(untitled) (Heritage, 2021)
Voltaire and Derrida made a great step towards post-modernism. Although they belong to different orientations, they contributed to the development of post-modernism a lot. Both of them carried out a tremendous criticism of the previous orientations, but they could not ignore some similarities. Voltaire carried out the criticism of pre-modernism by making the criticism of church, metaphysics and mystics. He attributed great role to the God in the sense of world creation, and he considered the c church as the institution which contradicted to common sense. He also gave some importance to supplements in his text writing. The appearance of Derrida in the middle of 1960s and especially of his work Of Grammatology, made a turning point in the development of social thinking in Europe. As the reaction to many modern explanations, his theory meant a new structure and dynamics of social thinking. His criticism was founded on the new role of texts in the triangle of writer, text and reader. All was founded on deconstruction where key term is difference. Different reading of text is important so as to see through the meaning of it.